Sex‐specific contribution of DHEA‐cortisol ratio to prefrontal‐hippocampal structural development, cognitive abilities and personality traits. (28th January 2019) - Farooqi, Nasr A. I.; Scotti, Martina; Yu, Ally; Lew, Jimin; Monnier, Patricia; Botteron, Kelly N.; Campbell, Benjamin C.; Booij, Linda; Herba, Catherine M.; Séguin, Jean R.; Castellanos‐Ryan, Natalie; McCracken, James T; et al.
Abstract: Although dehydroepiandrosterone (DHEA) may exert neuroprotective effects in the developing brain, prolonged or excessive elevations in cortisol may exert neurotoxic effects. The ratio between DHEA and cortisol (DC ratio) has been linked to internalising and externalising disorders, as well as cognitive performance, supporting the clinical relevance of this hormonal ratio during development. However, the brain mechanisms by which these effects may be mediated have not yet been identified. Furthermore, although there is evidence that the effects of cortisol in the central nervous system may be sexually dimorphic in humans, the opposite is true for DHEA, with human studies showing no sex‐specific associations in cortical thickness, cortico‐amygdalar or cortico‐hippocampal structural covariance. Therefore, it remains unclear whether sex moderates the developmental associations between DC ratio, brain structure, cognition and behaviour. In the present study, we examined the associations between DC ratio, structural covariance of the hippocampus with whole‐brain cortical thickness, and measures of personality, behaviour and cognition in a longitudinal sample of typically developing children, adolescents and young adults aged 6‐22 years (N = 225 participants [ F = 128]; 355 scans [ F = 208]), using mixed effects models that accounted for both within‐ and between‐subject variances. We found sex‐specific interactions between DC ratio and anterior cingulate cortex‐hippocampal structural covariance, with higher DC ratios being associated with a more negative covariance between these structures in girls, and a more positive covariance in boys. Furthermore, the negative prefrontal‐hippocampal structural covariance found in girls was associated with higher verbal memory and mathematical ability, whereas the positive covariance found in boys was associated with lower cooperativeness and reward dependence personality traits. These findings support the notion that the ratio between DHEA and cortisol levels may contribute, at least in part, to the development of sex differences in cognitive abilities, as well as risk for internalising/externalising disorders, via an alteration in prefrontal‐hippocampal structure during the transition from childhood to adulthood.